Club Chi a feasibilty study on an energy-generating green gym - Balmaceda, Angelo Ramon; Tan, Anna Melissa; Tan, Grace Anne; Yap, Bianca Larisa
The growth in population leads to an increasing need for alternative energy sources. There are new and innovative sources of energy being developed to substitute for finite fossil fuel sources. The bigger trend in relation to the development of alternative energy sources is that of going green. With issues such as climate change and global warming, everyone, from the individual consumer and multinational companies, is becoming concerned with environmental responsibility and reducing his or her carbon footprint. Another thing people are becoming concerned about is what they do to their bodies. This awareness is brought about by the increase in lifestyle-related diseases like diabetes and obesity. People now want to participate more in sports and fitness activities, which brings about a rise in sports groups, health clubs and gyms. Club Chi aims to combine the trend of going green and overall wellness into one fitness center where you can work out and contribute something to the environment at the same time, through specialized cardio machines that harness the human energy from the gym-goers' movements and convert it into electrical energy that can be fed back into the gym's electrical grid. Aside from these specialized cardio machines. Club Chi will also employ other green facilities such as efficient water systems and low-energy consumption lights to add to strengthen the value proposition of the gym, as well as to add to the overall green atmosphere. The possible market of Club Chi was segmented into a specific target market; those in Class A and B residing in Makati City, aged 30-39. This market was found to be most likely interested in engaging in sports activities and to have great concern for environmental causes. To further capture this market. Club Chi has three main product strategies: its novelty, the opportunity for goodwill and the opportunity to engage in corporate social responsibility. It will place itself in a strategic, convenient location in a condominium in Taguig City. A few channels to reach the market will be through social networking and media, promotions. Monthly gym membership will be priced competitively at PhP2.700, with a Php7OO/hour fee for a trainer. The facility of Club Chi will be located in an 18mx18m area, and will contain one office area, 2 locker rooms, a floor space for stretching and a main gym floor for the exercise machines. The specialized cardio machines will be imported from manufacturers from the United States, to ensure top efficiency and performance. Other gym machines, such as weights and strength equipment, will be bought locally. The gym will be open from Monday to Saturday, 6 AM to 10 PM and Sunday, 9 AM to 5 PM. For each shift, it will have on duty 1 trainer, 1 receptionist, 1 maintenance personnel and 1 security guard. 1 manager will oversee all operations. After a quick financial analysis, it is seen that the investment seems like a worthy one. The net present value at a MARR of 10% was positive, which indicates a profitable project. For a business in an industry where the payback period for an investment is normally more than 10 years. Club Chi's payback period is estimated to be between 6 and 7 years. Nowadays, people are looking for convenient ways to make a difference, and Club Chi provides one such venue. It provides its customers with social, environmental and physical wellness, with a place to care for their bodies as well as for the environment. Results of the study reveal that this business is feasible.